Challenges Of Women In Accessing Higher Education In India (Journal of Namibian Studies : History Politics Culture, 2023)
This abstract provides a succinct overview of the multifaceted challenges faced by women in India when striving to access higher education. The pursuit of higher education is a crucial avenue for personal growth, economic empowerment, and societal progress. However, in the Indian context, gender disparities persist, hindering women's ability to access and thrive in higher education institutions.This paper examines the numerous challenges that women encounter on their educational journey in India. It delves into the socio-cultural norms and expectations that often discourage families from supporting female education, emphasizing the preference for early marriage and domestic roles. Additionally, this research explores the economic barriers faced by many women, as they struggle to afford tuition fees, books, and transportation, particularly in lower-income households.Furthermore, the study investigates safety concerns and harassment on campuses, which deter many women from pursuing higher education or result in them dropping out prematurely. Institutional and policy-level challenges are also discussed, including inadequate representation of women in academic leadership roles, limited availability of gender-sensitive facilities, and a lack of comprehensive support systems.